1984
DOI: 10.1103/physrevlett.52.823
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Beam Nonuniformity Smoothing Due to X Radiation in Laser-Driven Layered Targets

Abstract: The effect of laser-beam spatial modulations on plane targets is analyzed as a function of modulation scale length and target material by means of x-ray shadowgraphy. At short laser wavelength it is shown that lateral energy smoothing is clearly improved because of the strong x-ray emission from the irradiated high-Z side of layered targets. The results, interpreted in terms of radiation-driven thermal transport, are in agreement with numerical simulations. PACS numbers: 52.50.Jm, 44.40. + a, 52.25.Fi, 52.55.Mg Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 12 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…In various previous works, hybrid schemes have been considered where initial x-ray illumination reduces the imprint of directly driven targets [5,6,7]. More recently, in work at NRL's Nike facility, Obenschain et al, [8] showed that direct drive laser imprint can be virtually eliminated in planar targets through the use of shaped laser pulses and thin high-Z layer ablation coatings.…”
Section: Security Classification Of: 17 Limitation Of Abstractmentioning
confidence: 99%
“…In various previous works, hybrid schemes have been considered where initial x-ray illumination reduces the imprint of directly driven targets [5,6,7]. More recently, in work at NRL's Nike facility, Obenschain et al, [8] showed that direct drive laser imprint can be virtually eliminated in planar targets through the use of shaped laser pulses and thin high-Z layer ablation coatings.…”
Section: Security Classification Of: 17 Limitation Of Abstractmentioning
confidence: 99%
“…First, there is laser-side surface roughness due to limitations in target fabrication. Second, perturbations are constantly supplied by the inevitable spatial nonuniformities in the laser beam, [2][3][4][5] which are imprinted into the flow through lateral nonuniformities of driving pressure. Considerable efforts are made to reduce the perturbations due to both sources through advancement of the target manufacturing technology and optical smoothing of laser beams.…”
Section: Introductionmentioning
confidence: 99%
“…The seed for the ablative RTI is provided by limitations in target fabrication, and by the imprint [2][3][4] of inevitable spatial nonuniformities in the laser beams. If the laser has been optically smoothed, then the imprint can be very small, but it can never be completely eliminated and is generally larger than target nonuniformities resulting from the manufacturing process.…”
mentioning
confidence: 99%